Art 32 Basel : The Art Fair. - Gagnebin, Georges; Keller, Samuel; Art Basel 2001 (Ostfildern-Ruit : Hatje Cantz Verlag, 2001)
Abbott, Berenice ; Acconci, Vito ; Ackermann, Rita ; Adler, Amy ; Ahtila, Eija-Liisa ; Aitken, Doug ; Aláez, Ana Laura ; Albers, Josef ; Alechinsky, Pierre ; Altenburger, Stefan ; Alÿs, Francis ; Andre, Carl ; Anselmo, Giovanni ; Antonakos, Stephen ; Appelt, Dieter ; Arcangeli, Maurizio ; Armajani, Siah ; Armleder, John ; Asdrubali, Gianni ; Badur, Frank ; Baer, Jo ; Baldessari, John ; De Barros, Geraldo ; Bartolini, Massimo ; Baselitz, Georg ; Baumeister, Willi ; Becher, Bernd & Hilla ; Beck, Lawrence ; Berchem, Otto ; Biberstein, Michael ; Bick, Andrew ; Blake, Jeremy ; Blazy, Michel ; Boberg, Oliver ; Bochner, Mel ; Boetti, Alighiero ; Boller, Reto ; Bornefeld, Julia ; Botto & Bruno ; Bourgeois, Louise ; Bowers, Andrea ; Bradley, Slater ; Braeckman, Dirk ; Brandl, Herbert ; Braque, Georges ; Brecknell Turner, Benjamin ; Brown, James ; Burden, Chris ; Buren, Daniel ; Burkhard, Balthasar ; Burmester, Gerardo ; Bustamante, Jean-Marc ; Calder, Alexander ; Calle, Sophie ; Caslin, Matthew Mc ; Castellani, Enrico ; Cecchini, Loris ; Celmins, Vija ; Cernicky, Jiri ; Charlton, Alan ; Chen Zhen ; Chen, Shaoxiong ; Chillida, Eduardo ; Chryssa ; Claerbout, David ; Cooper, Diana ; Coplans, John ; Costi, Rochelle ; Cragg, Tony (Anthony) ; Creed, Martin ; Crewdson, Gregory ; de Crignis, Rudolf ; Currin, John ; Damasceno, José ; Deacon, Destiny ; Dean, Tacita ; Delvoye, Wim ; Dias, Antonio ; Dollinger, Olivier ; Donaldson, A.D.S. ; Dopitová, Milena ; Dorner, Helmut ; Dragset, Ingar ; Dubreuil, Jean-François ; Duck-Hyun, Cho ; van Elk, Ger ; Eller, Thomas ; Elmgreen, Michael ; Ernst, Max ; Exter, Alexandra ; Fabre, Jan ; Fautrier, Jean ; Feininger, Lyonel ; Fischer, Urs ; Riverhead (New York) ; Fleury, Sylvie ; Fontana, Lucio ; Francis, Sam ; Frank, Robert ; etc.
Duits
Engels
Frans
Italiaans
Art 32 Basel : The Art Fair / Die Kunstmesse / La Foire d'art / La Mostra d'arte, Messe Basel, 13 - 18.6.2001
boek